Repeat Voting in the 2018 Cirebon Mayoral Election: Examining the Contributing Factors and the Professionalism of Cirebon's Electoral Commission (KPU) - Dian Fitriyani; Nur Hidayat Sardini; Dewi Erowati (Publikasi Indonesia, 2024)
Elections are essential democratic processes that require integrity, professionalism, and adherence to electoral laws. However, the 2018 Cirebon Mayoral Election faced allegations of electoral malpractice, leading to a re-voting order by the Constitutional Court. This research analyzes the Re-voting events in the 2018 Cirebon Mayor and Deputy Mayor Elections. There were allegations of fraud committed by election organizers in Cirebon raised by the Bamunas Setiawan and Effendi Edo candidate pairs. However, the existence was denied by the Cirebon City KPU at the case title of the dispute hearing on the results of Pilwakot Cirebon 2018 at the Constitutional Court of the Republic of Indonesia. This research focuses on analyzing qualitative studies with a case study strategy. Data obtained through literature study. This phenomenon is pure negligence in electoral governance by the KPU, which disrupts professionalism in the institution.